2016
DOI: 10.1039/c6tx00253f
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a tool to evaluate the toxicity of formulations containing amphotericin B, an antileishmanial drug

Abstract: Amphotericin B (AmB) is a drug of choice against life-threatening systemic fungal infections and an alternative therapy for the treatment of all forms of leishmaniasis. It is known that AmB and its conventional formulation cause renal damage; however, the lipid formulations can reduce these effects. The aim of the present study was to identify metabolic changes in mice treated with two different AmB formulations, a nanoemulsion (NE) (lipid system carrier) loaded with AmB and the conventional formulation (C-AmB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Therefore, it can be postulated that butanol and butanal metabolites, especially 3-hydroxybutyric acid, play an important role in the parasite metabolism and the leaf extract of X. stumarium inhibits the growth of Leishmania promastigotes by disrupting this metabolic pathway and inhibiting ATP supply. Our results are supported by previous finding (31).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, it can be postulated that butanol and butanal metabolites, especially 3-hydroxybutyric acid, play an important role in the parasite metabolism and the leaf extract of X. stumarium inhibits the growth of Leishmania promastigotes by disrupting this metabolic pathway and inhibiting ATP supply. Our results are supported by previous finding (31).…”
Section: Discussionsupporting
confidence: 94%
“…No significant study was observed on the role and probable importance of butanol and butanal in the maintenance and survival of promastigotes. The previous metabolomics-based investigation, confirmed 3-hydroxybutyric alteration in mice treated with new amphotericin B drug compound (31). This drug compound had less toxic effects on patients with Leishmaniasis (32).…”
Section: Discussionmentioning
confidence: 59%
“… 8 In human patients, metabolic profiles correlate with the presence and prognosis of neoplastic and cardiovascular diseases, 9 , 10 and can be further used to predict adverse effects and facilitate early discontinuation of ineffective or harmful treatments. 11 Advances in metabolic profiling are thereby paving the way for individualized medicine and therapeutic drug targeting. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Renal and hepatic function deterioration is a serious side effect limiting the use of AmB, even in commercial formulations, 62,71 its consequences being well documented in the literature. 18,71,79–81 For instance, hemorrhage, coagulative necrotic areas and the presence of pale hepatocytes as well as single-cell necrosis of hepatocytes with neutrophil aggregation have been observed in the livers of mice treated with Fungizone®. 71,81 Free-AmB seems to promote mild necrotic hepatocytes with moderate infiltration of the portal tract by inflammatory cells in mouse livers.…”
Section: Resultsmentioning
confidence: 99%
“…71,81 Free-AmB seems to promote mild necrotic hepatocytes with moderate infiltration of the portal tract by inflammatory cells in mouse livers. 80 In the case of the nephrotoxicity, AmB can promote renal vasoconstriction (which reduces the renal blood flow and glomerular filtration rate 79 ) and decrease the viability of renal tubular epithelial cells through alterations in cell membrane permeability, via pore formation, 82,83 promoting tubular necrosis. 18 Also, degenerative changes of renal glomerular tuft associated with abundant inflammatory cell infiltrates and intercellular edema has been observed.…”
Section: Resultsmentioning
confidence: 99%